Letters from Paris and Architect Dušan Grabrijan's Archive - Bogo Zupančič (Docomomo Journal)
The article presents the archive of architect Dušan Grabrijan at the Museum of Architecture and Design (MAO) in Ljubljana. It describes one of the key moments in the modernization of Slovenian (and Yugoslavian) architecture and society in the 1930s, namely the “invasion” of Le Corbusier’s studio at 35 Rue de Sèvres in Paris by Jože Plečnik’s students. The article primarily focuses on Grabrijan’s correspondence with architects Juraj Neidhardt and Milan Sever, who wrote to Grabrijan in Sarajevo from Paris. Four letters sent to Grabrijan from Paris are just a fraction of the extremely varied and extensive archive, testifying to the influence that the studio in Paris had on the architectural developments in Slovenia. Grabrijan’s archive is one of MAO’s largest. It comprises various materials, from sketches, letters, lecture notes, and official documents to different photographs and similar. The materials from the 1920s relate to Grabrijan’s study of architecture in Plečnik’s seminar at the Technical Faculty in Ljubljana and at École national supérieure des beaux-arts de Paris (ENSBA Paris). Materials from his Sarajevo period date back to 1930-1945, when Grabrijan served as professor at Secondary Technical School (STS) and was fascinated by Bosnian architecture, observing parallels with modernist architecture. The last period offers an insight into the years between 1945 and 1952 when Grabrijan was a professor at the Department of Architecture at the Technical Faculty in Ljubljana. After Grabrijan’s death in 1952, the archive was kept by his wife, who organized the publication of his books and their translations into foreign languages. These documents shed light on extensive architectural connections between Paris, Sarajevo, Ljubljana as well as Zagreb and Belgrade; the authors comment on architectural developments in their circles and on architects with whom they interacted.